Perceived value towards Melaka River Cruise influencing customer retention / Rafidah A. Raof and Hasnida Ramli - A. Raof, Rafidah; Ramli, Hasnida (2013)
This paper presents an exploratory research on perceived values towards customer retention in Malacca River Cruise. Customer perceived value has a subjective nature, since it means an evaluation judgment. In the literature review, it has been noted that the value received by customer has a number of components that determine its significance. The literature has also highlighted the existence of a relationship between perceived value and customer retention. The perceived values related to values of Physical Evidence, Process, Personnel and Image categorized as Independent Variables in this study are important factors influencing the dependent variable which is Customer Retention. Customer retention is an indicator for a business to measure how loyal the customers are and it is important to business since satisfied retained customers tend to spend more, cost less and make valuable references to new potential customers. The objective of this research paper is to determine the significant relationship of each independent variable (physical evidence value, process value, personnel value and image value) and dependent variable (customer retention). Totally, 100 copies of questionnaires have been distributed to the tourists/respondents at Taman Rempah and Muara Jetty and their surround areas. The method of collecting data is Convenience Sampling Method with non-probability technique. The collected data are analyzed using statistical program tool which is SSPS 21. Data are presented into Table of Correlation and Regression Analysis. The results from the analysis show only Physical Evidence, Process Value and Image Value are having the significant relationship with customer retention while Personnel Value have no significant relationship between customer retention even though the mean of Personnel Value are high as compared to other variables . Therefore, three objectives of this research are supported by the hypotheses. Whereby the hypotheses are accepted as the three variables (physical evidence value, process value, personnel value and image value) have significant relationship with customer retention. Finally, recommendations are proposed to improve services of Malacca River Cruise.